Evaluation of Dissociative Experiences in Forensic Medicine Practice and in the Criminal Justice System: Turkey Sample - deniz, derya (My University, 2019)
Comparing with the other disorders, dissociative disorders are mostly neglected in the criminal justice system. However, many people with dissociative disorders are frequently seen in the justice system rather than the health system. The issue to be considered here is that dissociative disorders may partially or fully affect one's freedom of consciousness and movement. The aim of this research is to investigate the way in which dissociative processes are dealt with in forensic medicine applications and to obtain descriptive and distinctive information about their psychological processes. The research were gone through with suspects and arrestees who are sent to Assembly of the Council of Forensic Medicine for psychiatric observation, by court order. Clinical and Sociodemographic Data Form, Childhood Trauma Questionnaire (CTQ) and Dissociative Experiences Scale (DES) were extended to the participants. A statistical evaluation were made on the research findings. According to the results of the research, % 30 of the participants had significantly high Dissociative Experiences Scale score. Also the prevalence of criminals having dissociative experiences is higher than the general population and clinical sample. From this perspective, it might be asserted that forensic occasions need a structured and unchanging approach that consider dissociative experiences inevitably.